2018
DOI: 10.3766/jaaa.17050
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Adults with Severe Hearing Loss

Abstract: The present data suggest that the range of abilities of an individual can be more fully captured with comprehensive testing. Such testing also offers an opportunity for informed counseling regarding realistic expectations for hearing aid use and the availability of hearing assistive technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
1
13
0
2
Order By: Relevance
“…Mean and standard deviation SRR thresholds for the YNH group were 4.35 (SD=1.35) cycles per octave. Thresholds were consistent with young listeners with normal pure-tone thresholds tested using the same paradigm reported previously (Souza et al, 2014). Thresholds could not be obtained for one listener in the YNH group, reducing the total number of subjects included in YNH group to eight.…”
Section: Resultssupporting
confidence: 89%
“…Mean and standard deviation SRR thresholds for the YNH group were 4.35 (SD=1.35) cycles per octave. Thresholds were consistent with young listeners with normal pure-tone thresholds tested using the same paradigm reported previously (Souza et al, 2014). Thresholds could not be obtained for one listener in the YNH group, reducing the total number of subjects included in YNH group to eight.…”
Section: Resultssupporting
confidence: 89%
“…Spectral ripple assesses the highest spectral modulation rate the listener can use to discriminate a modulation phase reversal, and studies that found a relationship between spectral ripple and speech had many listeners for whom that maximum modulation rate was below 2 rpo. 3,46,48 Studies that directly compared ripple discrimination with detection at 2 rpo showed that 2 rpo thresholds-not spectral ripplepredicted speech understanding in quiet and noise for cochlear implant (CI) listeners. 53,58 Davies-Venn et al 50 evaluated spectral ripple, spectral modulation detection, and frequency selectivity using psychophysical tuning curves.…”
Section: Spectral Ripplementioning
confidence: 99%
“…In a recent study, 3 frequency selectivity was evaluated in listeners with severe hearing loss using a spectral ripple discrimination task. 46,48 Ripple stimuli were generated from 800 sinusoidal components logarithmically spaced between 100 and 5,000 Hz.…”
Section: Spectral Ripplementioning
confidence: 99%
See 2 more Smart Citations